Морфологические особенности черепа и рогов гибридного асканийского оленя благородного степного - Кравченко, Р.С. (Вестник зоологии, 1971)
The peculiarities are studied of skull and horn structure of hybrid Askaniya-Nova deer. As a result of its comparison with the initial forms: Cervus elaphus brauneri, Cervus elaphus elaphus, Cervus elaphus maral, Cervus elaphus canadensis, Cervus elaphus sibiricus a conclusion was made that Askaniya-Nova steppe Cervus elaphus is identical with none of the initial forms. It has hereditary characters of some races; by the complex of characters it is most close related to Cervus elaphus sibiricus.